The Influence of Capital Structure, Company Growth and Company Value on Share Prices in Coal Sub-Sector Companies Listed on the Indonesian Stock Exchange 2018-2023 - Bhuana, Hendrie Satria; Hertina, Dede (GoAcademica Research & Publishing, 2024)
This study aims to empirically investigate the impact of Capital Structure, Company Growth, and Company Value on stock prices. Employing a quantitative descriptive research method with a verificative approach, the study utilizes panel data regression analysis to examine these relationships. The research focuses on Coal Sub-Sector Companies listed on the Indonesia Stock Exchange from 2018 to 2023, encompassing a sample of 12 companies. The findings reveal that Capital Structure negatively influences stock prices, indicating that higher debt levels may detract from stock value. Conversely, Company Growth is found to have no significant effect on stock prices, suggesting that growth metrics do not necessarily translate to market valuation in this sector. In contrast, Company Value exerts a positive impact on stock prices, demonstrating that higher valuation metrics are associated with increased stock prices. These results provide valuable insights for investors and stakeholders in the coal sub-sector, highlighting the critical factors that drive stock price movements and offering a basis for more informed investment decisions.